Determining the Optimum Values of the Mixing and Floc Formation Parameters When Air Mixing is Used in Surface Water Purification Processes - صبوح, حسام (Latakia University Journal -Engineering Sciences Series, 2021)
The research is summarized in conducting a wide series of laboratory experiments in order to determine the optimal values ​​ of the mixing and floc formation parameters when air mixing is used to accomplish both processes. These parameters are represented by the continuity of each of the mixing processes (T1, sec) and floc formation (T2, sec), as well as The intensity of the mixing process for each of them, which is expressed by the so-called mixing velocity gradient coefficient (G1, sec-1) and the mixing velocity gradient coefficient (flake formation) (G2, sec-1). The research presented briefly to the theoretical foundations of the processes of purifying drinking water from surface sources, which include the methods and quality of facilities used to treat drinking water, as well as the concept of the ongoing coagulation process when using chemicals in natural water treatment processes and the factors affecting them. The methodology of conducting the research included the foundations and hypotheses adopted for the experimental work, as well as the parameters taken into account and their oscillation fields, in addition to the mechanism for organizing and conducting the experimental work and the equipment used for that. To shorten the number of experiments needed to reach the desired goal of the research, all experiments were conducted on water taken from the outskirts of one of the lakes of the Tishreen 16 Dam near the village of Mashkita. According to the turbidity of the raw water that will be subjected to treatment, using the experimental coagulation method (Jar-Test), the value of the required optimal dose of the chemical coagulant that was used in the experimental work was determined, which was hydrated aluminum sulfate [Al2(SO4)3.18H2O]. The results of the laboratory experiments were presented and represented graphically on charts that allowed discussion and analysis of those results, as well as reaching the optimal values ​​for the parameters of the mixing and floc formation processes presented above, which we explained in a special table according to the turbidity values ​​of raw water used in laboratory experiments. In conclusion, the conclusions reached through careful analytical reading of the test results were presented, which in turn allowed us to reach a number of recommendations that we see the importance of adopting in subsequent research in this field to develop a method for purifying drinking water taken from surface sources.